Brainstem reflexes and brainstem auditory evoked responses in Huntington's chorea. Issue 3 (March 1986) - Bollen, E; Arts, R J; Roos, R A; van der Velde, E A; Buruma, O J
Abstract : Blink reflex, corneal reflex, jaw reflex, exteroceptive suppression in masseter muscles and brainstem auditory evoked potentials were measured in 20 patients with Huntington's chorea and 12 controls. A significantly increased latency of the second component of the homolateral and heterolateral blink reflex was found in the patient group as compared with the controls. The other investigations revealed no significant differences between patients and controls except for some facilitation of the jaw reflex in the patient group. Increase of second component latency of the blink reflex in the presence of normal corneal reflexes is suggestive of functional impulse conduction disturbance in the lower brainstem. It is discussed whether in Huntington's chorea this is to be attributed to alterations of cortical or striatal influence or to local brainstem abnormalities.